AB0304 What Proportion of Patients Fail to Achieve Das, Cdai, Sdai Remission Based on Patient Global assessment? An Analysis from a Prospective, Observational Registry. (9th June 2015) - Baer, P.; Keystone, E.; Bensen, W.; Thorne, C.; Haraoui, B.; Choquette, D.; Arendse, R.; Kelsall, J.; Sheriff, M.; Sampalis, J.; Rampakakis, E.; Tkaczyk, C.; et al.
Abstract : Background: PtGA is included in the formula of all disease activity indices despite the fact that it may not accurately reflect RA disease activity, but rather reflect symptoms related to fibromyalgia, low back pain, depression or other conditions. We previously assessed the impact of the PtGA on the ability to achieve Boolean ACR/EULAR remission state. Objectives: The aim of this analysis was to assess the proportion of patients failing to achieve DAS, CDAI and SDAI remission based on a real-world, routine clinical care setting in Canada. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, AS, or PsA with IFX or GLM. In this analysis, RA patients treated with infliximab between 2002-2014 or with golimumab between 2010-2014 were included. Modified versions of DAS28 (mDAS28), CDAI (mCDAI), and SDAI (mSDAI) were calculated by omitting PtGA from the formulas. Correlation of the standard and modified versions of each index was assessed with the Pearson's correlation coefficient. In the absence of validated thresholds for remission and LDA for the modified versions, the standard definitions were considered as the gold standard and ROC curve analysis was used to identify new thresholds for the modified versions. Cross-tabulations with the Chi-square test were used to assess the agreement between the standard and modified definitions of remission and LDA. Results: One thousand nineteen RA patients with a mean (SD) age of 56.1 (13.5) years and disease duration of 8.5 (9.1) were included in the analysis. A strong correlation was observed between the standard and modified versions of DAS28 (r=0.98; P<0.001), CDAI (r=0.99; P<0.001), and SDAI (r=0.99; P<0.001). Based on ROC analysis the new thresholds for remission and LDA were: DAS28 (remission=2.6, LDA=3.1), CDAI (remission=2.5, LDA=10.5), SDAI (remission=3.3, LDA=10.9). Cross-tabulation of the standard and modified thresholds showed that an additional 10.1%, 10.6%, and 17.8% of non-remission cases for DAS28, CDAI and SDAI, respectively, would be classified as remission with the modified definitions. Similarly, an additional 11.5%, 21.2%, and 20.6% of non-LDA cases for DAS28, CDAI and SDAI, respectively, would be classified as LDA. Conclusions: The results of this analysis have shown that PtGA could account for up to 10% of non-remission cases and up to 20% of non-LDA cases as measured by DAS, CDAI and SDAI. Further analyses are required to identify the determinants of patient global assessment. Disclosure of Interest: P. Baer Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, E. Keystone Speakers bureau: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, W. Bensen: None declared, C. Thorne Consultant for: Janssen, B. Haraoui Grant/research support from: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, UCB, Consultant for: AbbVie, Amgen, BMS, Janssen, Pfizer, Roche, UCB, D. Choquette Consultant for: AbbVie, Amgen, Celgene, BMS Canada, Janssen, Pfizer, R. Arendse Consultant for: Janssen, J. Kelsall Consultant for: Janssen, M. Sheriff Consultant for: Janssen, J. Sampalis Shareholder of: JSS Medical Research, Employee of: JSS Medical Research, E. Rampakakis Employee of: JSS Medical Research, C. Tkaczyk Employee of: Janssen, M. Shawi: None declared, A. Lehman Employee of: Janssen, F. Nantel Employee of: Janssen, S. Otawa: None declared